A Review of Factors Affecting the Acquisition of Second Language Reading Skills - Shahbaz Haider; Aleem Shakir (Linguistics and Literature Review, 2023)
Effective reading skills are essential prerequisites for L2 reading proficiency which demand different metacognitive and cognitive skills to deal with the problems before and during the reading. These reading strategies adopted by L2 proficient readers are effective methods to handle the primary factors that influence reading proficiency. Therefore, the current research  provided a comprehensive review of factors affecting the acquisition of second-language reading skills. The review consisted of thirty-two research articles related to L2 reading acquisition. The results demonstrated primary factors which impacted the L2 reading skills and a wide range of reading techniques adopted by proficient English language learners to construct meanings from the written text. Finally, it is likely to expect that the review of factors affecting reading skills can provide English language teachers and English language learners with in-depth insights into social and cognitive factors affecting L2 reading literacy.